2006
DOI: 10.1017/s0025315406013725
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversity of larval skeletons in the sea urchin family Echinometridae (Echinoidea: Echinodermata)

Abstract: To clarify the morphological variety of larval skeletons, a detailed morphological comparison among the species of the family Echinometridae was performed. Through conspeci¢c comparison of larval skeletons among di¡erent ages, we found ¢ve skeletal characters of the body skeleton that are stable in the fourarmed pluteus and thus useful in homologous comparison among the species. The morphological variation was summarized as the di¡erence in the number of spines and posteroventral transverse rods, and di¡erence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Calcified skeletal elements of adult echinoids include test plates, jaw components (including teeth and pyramids) and spines, both primary and secondary. The feeding echinopluteus larvae of most echinoids have a basketshaped endoskeleton supporting the body and arm rods that support the larval arms (Emlet 1988, Kinjo et al 2006, which can be simple or fenestrated calcite rods, with the latter being more robust (Kinjo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Calcified skeletal elements of adult echinoids include test plates, jaw components (including teeth and pyramids) and spines, both primary and secondary. The feeding echinopluteus larvae of most echinoids have a basketshaped endoskeleton supporting the body and arm rods that support the larval arms (Emlet 1988, Kinjo et al 2006, which can be simple or fenestrated calcite rods, with the latter being more robust (Kinjo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…we first identified characters that are not affected by growth or food supply and thus are useful in homologous comparison among the species. We compared larval skeletons between different ages within the same species (2-vs. 4-day-old larvae of Echinometra oblonga and 2-vs. 5-day-old larvae of Colobocentrotus mertensii) and found that the elements of body-skeleton did not differ between different ages although the length of postoral rod significantly increased with larval age (Kinjo et al 2006). Thus, the characters of the body-skeleton can be regarded as typical for each species and useful for the homologous comparison among the species (Fig.…”
Section: Phylogenetic Analysismentioning
confidence: 96%
“…Also, many other morphological characters are quite similar, for example, the test structure, the shape of pedicellaria, and the larval skeleton (Smith 1988;Kinjo et al 2006). Thus, molecular and morphological characters suggest a close relationship between these two genera.…”
Section: Phylogeny Of the Echinometridaementioning
confidence: 99%
See 2 more Smart Citations